Leukemia-associated immunophenotype of tumor cells in childhood B-precursors acute lymphoblastic leukemia - L. V. Movchan (Онкогематология, 2014)
To allow minimal residual disease (MRD) monitoring using flow cytometry it is needed the optimal combination of monoclonal antibodies (MA), based on a precise knowledge of leukemic cells immunophenotypic features. Multiple immunophenotypic aberrations in leukemic blasts of B-precursors ALL (BII ALL) were revealed. Asynchronous expression of differentiation antigens on tumor cells occurs in more than 50 % cases. Aberrant myeloid markers expression in 42.6 % BII ALL cases was observed. The main differences between tumor and normal bone marrow cells are the expression intensity of CD19, CD10, CD20, CD38, CD45, CD34 and CD58. Thus, expression intensity pattern of CD19, CD10, CD20, CD38, CD45, CD34, CD58 on tumor cells compared with normal B-lymphocyte precursors allow to use these markers combination to MRD monitoring.